Question and Answers Forum

All Questions      Topic List

None Questions

Previous in All Question      Next in All Question      

Previous in None      Next in None      

Question Number 188418 by 073 last updated on 01/Mar/23

Answered by manxsol last updated on 01/Mar/23

T_n =i^(4n−3)   T_n =(i^(4n) /i^3 )=(((i^2 )^(2n) )/(−i))=(1/(−i))×(i/i)=  (i/((−1)(−1)))=i=T_n   4n−3=49  n=13  Σ_1 ^(13) i=13i

$${T}_{{n}} ={i}^{\mathrm{4}{n}−\mathrm{3}} \\ $$$${T}_{{n}} =\frac{{i}^{\mathrm{4}{n}} }{{i}^{\mathrm{3}} }=\frac{\left({i}^{\mathrm{2}} \right)^{\mathrm{2}{n}} }{−{i}}=\frac{\mathrm{1}}{−{i}}×\frac{{i}}{{i}}= \\ $$$$\frac{{i}}{\left(−\mathrm{1}\right)\left(−\mathrm{1}\right)}={i}={T}_{{n}} \\ $$$$\mathrm{4}{n}−\mathrm{3}=\mathrm{49} \\ $$$${n}=\mathrm{13} \\ $$$$\sum_{\mathrm{1}} ^{\mathrm{13}} {i}=\mathrm{13}{i} \\ $$

Answered by mehdee42 last updated on 01/Mar/23

(i)^(4n) =1  ⇒i+i^5 +i^9 +...+i^(49) =i+i+...+i=13i

$$\left({i}\right)^{\mathrm{4}{n}} =\mathrm{1} \\ $$$$\Rightarrow{i}+{i}^{\mathrm{5}} +{i}^{\mathrm{9}} +...+{i}^{\mathrm{49}} ={i}+{i}+...+{i}=\mathrm{13}{i} \\ $$

Terms of Service

Privacy Policy

Contact: info@tinkutara.com